2000
DOI: 10.1021/jf000246n
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Alkamides in Dried Echinacea purpurea

Abstract: Different drying methods, such as freeze-drying (FD), vacuum microwave drying (VMD), and air-drying (AD), were applied to fresh roots and leaves of Canadian-grown Echinacea purpurea to determine the optimal method for preserving alkamide levels. Using HPLC, six alkamide fractions (alkamides 1, 2, 3, 6a/6, 7, 8/9) were quantitated in dried roots, whereas four alkamide fractions (alkamides 1, 2, 3, 8/9) were measured in dried leaves. Different elution conditions used in HPLC for alkamide analysis did not affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Many alkamides have been isolated and identified from the roots and flowers of E. purpurea (Kim et al, 2000;Stuart & Wills, 2000;Binns et al, 2002;Clifford et al, 2002), with dodeca-2E,4E,8Z,10E-tetraenoic acid isobutylamide (alkamide 8) and dodeca-2E,4E,8Z,10Z-tetraenoic acid isobutylamide (alkamide 9) being predominant (Kim et al, 2000), particularly in the young tops (Qu et al, 2005). In the present study, alkamides 8 and 9 were detectable in flower heads, leaves and root portions of E. purpurea plants (Tables 3, 4, and 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many alkamides have been isolated and identified from the roots and flowers of E. purpurea (Kim et al, 2000;Stuart & Wills, 2000;Binns et al, 2002;Clifford et al, 2002), with dodeca-2E,4E,8Z,10E-tetraenoic acid isobutylamide (alkamide 8) and dodeca-2E,4E,8Z,10Z-tetraenoic acid isobutylamide (alkamide 9) being predominant (Kim et al, 2000), particularly in the young tops (Qu et al, 2005). In the present study, alkamides 8 and 9 were detectable in flower heads, leaves and root portions of E. purpurea plants (Tables 3, 4, and 5).…”
Section: Resultsmentioning
confidence: 99%
“…The contents of total phenolic, several caffeoyl derivatives, and alkamides were also determined and compared among the tested E. purpurea cultivars and selected populations. Various alkamides have been isolated and identified from the roots and flowers of E. purpurea (Binns et al, 2002), with dodeca-2E,4E,8Z,10E-tetraenoic acid isobutylamide (alkamide 8) and dodeca-2E,4E,8Z,10Z-tetraenoic acid isobutylamide (alkamide 9) being predominant (Kim et al, 2000). Therefore, only alkamide 8 and alkamide 9 were determined in the present study.…”
Section: Introductionmentioning
confidence: 98%
“…Livesey and others (1999) showed that chicoric acid was lost during storage conditions under 40 °C. The level of alkamide(s) retention in E. purpurea roots and leaves can also be variable, depending on the method used to dry product (Kim and others 2000b). These results indicated that temperature influences the retention of E. purpurea phytochemical biomarkers; good indicators of estimating herb quality as well as predicting functional activity for use as health remedies.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids (camphene, limonene, β -myrcene, ocimene, α -and β -pinene, terpene) predominated (i.e., 82 -91%) in the headspace analysis of volatile components from fl owers and stems, whereas headspace analysis of volatile components from roots contain 41 -57% aldehydes (2 -and 3 -methylbutanal, 2methylpropanal, 2 -propanal, acetaldehyde), alcohols, and 6 -21% terpenoids. 14 Alkamides occur in alcoholic extracts of the aerial parts and roots from E. purpurea and E. angustifolia . The major categories of chemicals in Echinacea species are alkamides and caffeic acid conjugates (caftaric acid, chlorogenic acid, cynarin, echinacoside, cichoric acid).…”
Section: Chemical Compositionmentioning
confidence: 99%